Optimizing Growing Condition And Planting Date For Growth, Yield And Quality Of Squash In Bangladesh (SAARC Journal of Agriculture, 2024)
An experiment was conducted at the Vegetable Research field of Horticulture Research Centre Division, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh, during October 2018 to March 2019 to find out the effect of growing condition and planting date on yield and yield attributes of squash. The experiment comprised two sets of treatments viz., (a) Growing conditions: (i) Open cultivation (C1); (ii) Net protected cultivation (C2) and Cultivation with barrier crop (C3) and (b) Planting dates: (i) 1 November (D1); (ii) 15 November(D2); (iii) 1 December (D3) and (iv) 15 December (D4) in a randomized complete block design (RCBD) with three replications. The variety BARI squash-1 was used in this experiment. The results showed that net protected cultivation showed significantly the highest fruit plant-1, fruit length, yield plant-1 and yield ha-1. Growing condition did not affect quality parameters of quash. Early planting (1 November) showed significantly higher yield, yield attributes and quality parameters than late planting. Fruit diameter did not showed any significant difference irrespective of planting date. The interaction between growing condition and planting dates was significant for yield and quality parameters. Based on the study results it is concluded that maximum yield (49.33 t ha-1) and quality of BARI squash-1 could be achieved through cultivation under net protected condition with 1 November planting.SAARC J. Agric., 22(1): 97-109 (2024)